Growth performance of Asian catfish (Clarias batrachus linnaeus) and water quality in recirculating aquaculture system - Fadhil, Rahmat (2012)
Strategies to increase fish production are always being done on a continuous basis from time to time to develop a new better system. Water quality management is required in aquaculture systems, as it can affect the production and the organisms that live in the water. The use of Recirculating Aquaculture System/RAS in the fishing industry is the latest challenge to the fishing communities and researchers. The use of multi-media filtrations to maintain healthy water quality for aquaculture remains an important issue to be studied. The main problem is how to maintain the water quality parameters for fish life until the harvest. In this study, the concept of the RAS has been developed to determine the ability of controlling the quality of water for sustainable aquaculture. This study aimed to develop catfish breeding in an integrated utility with optimal use of water and soil. The objectives of this study were: (1) to determine the growth rate of catfish with mechanical circulatory system and water quality control through a biological filtration unit, (2) to measure the water quality parameters of fish production tanks, and (3) to study the process and the way water can be mixed up,producing more stable water quality conditions in the unit culture and reducing contaminations. Asian catfish (C. batrachus) was cultured in three separate tanks, each with a size range of 5-8 cm (Tank 1), 8-12 cm (Tank 2), and 12-15 cm (Tank 3) for 30 days. Each tank contained 300 fishes. Water samples were analyzed twice (morning and afternoon) with duplicates during the experiment. Water quality parameters such as temperature, turbidity, dissolved oxygen, pH, and ammonia were measured. The entire tank was connected to water supply through a filter to each tank using PVC pipes. Resulting residues settled in a sedimentation tank. Water was pumped through the filter into a subsequent sedimentation tank and back into the tank through recirculation. Fish was fed at 3% of the total fish weight twice a day (morning and evening). The RAS and biological filter systems with multi-media and backwash capability have resulted in improved water quality for the intensive culture of catfish. Fish survival rate was above 95% with weight gain of catfish of 11.00+1.90 gram/fish in Tank 1, 20.45+0.85 gram/fish in Tank 2, and 25.65+0.95 gram/fish in Tank 3. Rate of increase in length and weight of catfish in Tank 1 was from 6.5+1.5 cm (1.00+0.10 gram) to 12.0+2.0 cm (12.00+1.80 gram), Tank 2 from 10.0+2.0 cm (2.10+0.60 gram) to 16.0+2.0 cm 22.55+1.15 gram), and Tank 3 from 13.5+1.5 cm (5.65+1.25 gram) to 18.5+2.5 cm (32.33+0.30 grams). Data analysis using Completely Randomized Design/CRD with three treatments and two replicates showed that the total percentage of survival of catfish in Tank 2 was higher than the other tanks. Percentages of survival from the highest to the lowest were 98.33%+0.33 (Tank 2), 95.33%+0.67 (Tank 1), and 95.17%+0.84 (Tank 3). ANOVA test showed no significant difference of water quality and growth performance between one tank and the rest in this trial. The results showed that RAS system can be successfully used and further developed to increase fish production, intensively. There was hardly a huge negative impact on water quality,growth, and survival rate of catfish in the tank for the period of observation. This indicates that differences in size of the fish in each tank did not have any great impact on the growth, survival, and quality of water in the catfish culture.